Representações sociais das professoras de alunos identificados como hiperativos incluídos no sistema regular de ensino de Santa Maria/RS - Luft, Sibila (2007)
This research was developed on the Line of Research Special Education of the program of post-Graduation in Education of the Education Center of the UFSM. Demands which were considered hard, among them hiperactive, negligent and undisciplined pupils with problems of behaviour make part of the school universe. But we perceived that the current legislation doesn´t contemplate and the school environment is indiferent to these pupils as being students with special education necessities. The Trouble of Deficit Attention Hiperactivity was recognized by medicine in the begining of the 20th century, of unknown etiology being the diagnosis only clinical (KEPLAN, 2002; BERKLEY, 2002). With this theme, of great social relevance, we made this resource with the aim of investigating the Social Representations of Teachers of the Pupils Identified as Hiperactive Enclosed at the Regular System of Teaching of Santa Maria/RS, in the direction of understanding the representations of the teachers and how it is occuring the inclusion of these pupils. For such a way, we used, as methodological criterion, the qualitative descriptive reasearch, envolving 8 teachers of the initial series of a state school of the basic education. In the collection of data,we used a semi-structural interview with seven questions, which were recorded and written in the complete one for posterior analyses of the content (BARDIN, 1977) and the participant observation (GIL, 1999). As theoric contribution, we tried to understand through the Theory of Social Representations (MOSCOVICI, 1978) the meaning of the representations of the teachers.The results show that the teacher´s representations concentrate in the behavioural and in the learning questions. Such pupils exist in fact, but they do not exist of right, what make them vulnerable to preconceptions and discrimination. Concerning to the education of these pupils, we observed the incentive to the individual work in detriment of the collective one. But through the teacher´s representations, this research also pointed an important and significant way upon the pupil´s education identified as hiperactive: the work developed with human values. We verified indications of inneficacy on the procedures used by the institution, concerning to the pupil´s evasion with problems of behaviour which caused patrimonial damages to the school environment.